Kekerabatan Bahasa Jawa, Bahasa Sunda, dan Bahasa Madura: Analisis Leksikostatistik dan Korespondensi Bunyi - Intan Pramesty Eka Sudarno; Angga Trio Sanjaya (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
Historical comparative linguistics is used as a tool to determine the relationship between languages in an effort to understand the origins or history of language formation in a particular region, as well as its development. The objective of this study is to identify the linguistic relationship between the Turi Sleman Javanese language, the Bogor Sundanese language, and the Bangkalan Madurese language using linguistic correspondence analysis, lexicostatistics to determine the kinship system, and glottochronology to determine the time of divergence. This study employs a combination of qualitative and quantitative methods, with data sources drawn from three speakers of the Turi Javanese, Bogor Sundanese, and Bangkalan Madurese languages. Data collection techniques include interviews, note-taking, and literature review. Data analysis techniques include sound correspondence, lexicostatistics, and glottochronology. The analysis results are presented in a descriptive format with data tables. The findings indicate that these three languages still belong to the same language family, with a linguistic kinship percentage of 30.5% between Javanese and Sundanese, 33% between Javanese and Madurese, and 31.5% between Sundanese and Madurese, with Javanese and Madurese showing a closer linguistic kinship. Additionally, the estimated divergence times for the three languages range from 2,471–3,165 years ago for Javanese and Sundanese, 2,404–2,852 years ago for Javanese and Madurese, and 2,503–2,961 years ago for Sundanese and Madurese, with the longest divergence period occurring between Turi Javanese and Bogor Sundanese. Thus, this study contributes to the body of knowledge on the phonological systems of Indonesian regional languages and demonstrates that immigration, geographical differences, and contact with other languages can consistently alter proto-languages. Keywords: language relationship, sound correspondence, lexicostatistics, glottochronology